The Effect of Online Gaming on Social Skills Development Among UTHM Students - Zulkafli, Nur Auni Qistina; Mohmad Rozi, Marlisa; Zakaria, Nur Annis Safrina; Sazeli, Zul Afiq; Ab Jabal, Mohamad Faizal (Multidisciplinary Applied Research and Innovation, 2026)
Online games are becoming more popular among students in higher learning institutions, or public universities, such as Universiti Tun Hussein Onn Malaysia (UTHM). Online games serve as a medium of entertainment as well as a platform for social interaction in a virtual space. However, there is a concern that online gaming may alter students' social skills in the real world, notably in terms of communication and collaboration. Social skills are how a person can interact with other people effectively in different situations; social skills also play a key role when an individual is looking to achieve academic, professional, or career success. For the case of students, face-to-face interaction can form self-confidence, build leadership, and teamwork abilities, while an online game perspective may align players to interact in a virtual environment where the opportunities to create and build social skills are diminished. This research study was conducted to identify the impact of online games on students' social skills, specifically on UTHM diploma students’ communication and teamwork skills. A questionnaire instrument was used to collect data and was conducted on a total of 301 students to collect responses. Respondents were selected based on the Krejcie and Morgan table. Data analysis was completed using SPSS, and the Pearson correlation and independent t-test were utilized. Results of this study indicate that there is relationship between online gaming and social skills students, which is the correlation is 0.280, 0.426, and 0.227 and gamers show significantly higher social skills than non-gamers. Also, the result for sample independent t-test of section 2 is 0.001 and section 3 is